Design thinking toolkit for UAT - Lehto, Mila (2024)
This study emerges in the themes of design thinking, user involvement and acceptance testing in software development. Since design thinking is a mindset it has worked as a lens throughout the process of writing this thesis. The theory presents the principles and processes of design thinking to make readers familiar with the perspective of design, which is very different from the usual in the technology world. User acceptance testing is also viewed through the definition and its design process, noting the role of the user. Later in the literature review, the user's role and involvement in UAT and software development in general is examined thoroughly, pointing out the issues and challenges that are raised, as well as the benefits it can cause when properly implemented. To answer the challenges and to ensure the benefits, the research explores user involvement in design thinking and significance of giving users tools to provide necessary information. The study presents a solution for the issues that are faced in user acceptance testing by providing a set of design thinking tools, that provide value in UAT process.